Impact of Supply Chain Leadership and Supply Chain Fellow Ship on the Productivity and Performance Dynamics in Pharmaceutical Industry of Indonesia - Khalik, A; A. Musyaffa, A; Ali, Hapzi (ExcelingTech, 2020)
This study is to analyze the effect of supply chain leadership and supply chain fellow ship on the productivity and performance of pharmaceutical industry of Indonesian economy. The population in this study are the core employees who are working in the pharmaceutical industry of Indonesia and primarily responsible for managing different supply chain related activities with their management interaction as well. The approach in this study uses a quantitative approach to the survey method and uses path analysis with Statistical Package for Social Science (SPSS) 21.0. The results of the study through quantitative analysis showed that supply chain leadership and supply chain followership had a positive and significant influence on the productivity and performance factors in the pharmaceutical industry of Indonesia. Based on the study findings, it is suggested that business managers, supply chain officials and other decision makers need to consider the impact of two newly dimensions of supply chain on the firm performance and productivity factors as well. However, the relationship of supply chain leaderhsip and followrship with the various categoreis of teh suppliers in teh pharmaceutical indsutry is entirey missing. In addition, the smaple size of the current study is very limited and can be expanded with more efforts in the future studies. Additonaly, this study is only applied to one sector from the whole economy of Indonesia which indicates that future studies needs to expand their implication in terms of cross sectional reserach desing. Finally, this study has considered any type of demogrphaic factors which are quite important to examine the respondent profile. It is suggested that upcoming studies need to examine these limitations for the better implications and more origanlity as well.